Outbreaks of COVID-19 in a tuberculosis treatment sanatorium on the Thailand-Myanmar border: a retrospective cohort analysis [version 2; peer review: 1 approved, 2 approved with reservations] - Wanitda Watthanaworawit; Gornpan Gornsawun; François Nosten; Makoto Saito; Lei Lei Swe; Win Pa Pa Tun; Sophie Lesseps; Aung Than; Banyar Maung Maung; Napaporn Kaewphanderm; Htet Ko Ko Aung; Aung Pyae Phyo; et al. (Wellcome Open Research)
Background Tuberculosis (TB) is a chronic condition, with overlapping symptoms to those of coronavirus disease 2019 (COVID-19). There has been inconsistent evidence on whether TB is a predisposing factor for developing severe COVID-19. The aim of this report is to explore whether TB influences the severity of COVID-19. Methods COVID-19 cases at two TB sanatoria on the Thailand-Myanmar border were reviewed. Demographic, clinical and laboratory data including TB treatment and co-morbidities, were analyzed. Characteristics and COVID-19 clinical outcomes were compared between two groups of patients: TB and those without TB (the caretakers and the medical personnel). Multivariable ordered logistic regression was conducted to compare the risk of severe COVID-19 between the two groups. Results Between September 2021 and March 2022, 161 COVID-19 cases were diagnosed. Over half of the COVID-19 patients were infected with TB (n= 104, 64.6%), and the rest were not (n=57, 35.4%). The median (interquartile range) age was 48 (33.5-57.0) and 27 (23-33) years in the TB and in the non-TB COVID-19 patients, respectively. Before COVID-19 infection, 67.1% (106/158) of patients had received at least one dose of COVID-19 vaccine. The median cycle threshold value at diagnosis was not different between TB (18.5, IQR 16.1-32.3) and non-TB patients (18.8, 15.1-30.0). Fever, gastrointestinal symptoms and ageusia were more common in non-TB patients. Six patients (3.8%, 6/156) all from the TB group became severe of which five (3.2%, 5/156) required oxygen therapy. One TB patient died (1/104, 0.96%) of lung cancer. After adjustment for potential confounders, the final clinical severity was not different between the two groups (adjusted odds ratio 1.40, 95% confidence interval 0.16–12.39). Conclusions TB was not associated with severe outcomes in the two TB sanatoria. The high uptake of COVID-19 vaccination and active screening could have impacted on disease progression and prevented unfavorable outcomes.